Lof Genre and its Artistic Features - D. U. Mekhlieva (Researchparks Publishing, 2022)
In the article, lof – genre of uzbek oral folks arts, has been studied on the basis of theoretical data from the scientific and artistic perspective. It discusses the differences between lof and other genres based on the structure of lof, its specific composition, critical features, and its relation to humor and joke.